Криозащитные свойства растворов на основе непроникающего ОЭГ n=25 в комбинации c проникающими криопротекторами при замораживании эритроцитов человека - Pakhomova, Yuliya S.; Chekanova, Valentina V.; Kompaniets, Antonina M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
Cryoprotective efficiency of сryopreservatives, based on combination of extracelular cryoprotectant oxyethylated glycerol with polymerization degree n = 25 (OEGn=25) with penetrating cryoprotectants 1,2-propanediol (1,2-PD), dimethyl sulphoxide (DMSO) and dimethyl acetamide (DMAc) during red blood cells freezing was studied. Freeze-thawing in solutions of OEGn=25 and 1,2-PD, DMSO and DMAc mixed in 5:1 ratio, as well as with DMAc in ratios of 2:1 and 1:1 resulted in the reduction of osmotic fragility of red blood cells comparing to non-treated cells. The highest level of post-thaw survival of red blood cells according to indices of hemolysis and content of free hemoglobin was found for 30% OEGn=25 solution.